Preparation method, treatment device and application of heterogeneous catalysis electro-Fenton reaction material

By loading FeSO4 and EDTA on columnar activated carbon, heterogeneous catalytic electrofenton reaction materials are formed and a treatment device is constructed, which solves the acid-base consumption and iron sludge treatment problems of the traditional Fenton method in wastewater treatment, and achieves efficient and low-cost deep treatment effect of wastewater.

CN119612695AInactive Publication Date: 2025-03-14CCCC TIANJIN ECO ENVIRONMENTAL PROTECTION DESIGN & RES INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411636778.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The traditional Fenton method has problems such as large acid and alkali consumption, difficulty in treating iron sludge, low utilization rate of H2O2 and Fe2+ in wastewater treatment, and the catalytic efficiency of heterogeneous Electro-Fenton system is low and costly.

Method used

Using columnar activated carbon as a support, by removing surface ash, grease and inorganic salts, loading FeSO4 and EDTA, a heterogeneous catalytic electrofenton reaction material is formed, and a heterogeneous catalytic electrofenton treatment device is constructed for deep wastewater treatment.

Benefits of technology

An efficient COD removal rate is achieved, reaching ≥80%, and the average COD concentration after wastewater treatment is <25mg/L, which meets the industrial circulating water replenishment standards. It has low material cost, long service life, and no pH adjustment is required, which reduces acid and alkali salt consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612695A_ABST
    Figure CN119612695A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a heterogeneous catalysis electro-Fenton reaction material, a treatment device and application. The preparation method of the heterogeneous catalysis electro-Fenton reaction material comprises the following steps: measuring columnar activated carbon and removing ash on the surface of the columnar activated carbon; removing grease and inorganic salt in the columnar activated carbon; cleaning and drying the treated columnar activated carbon to obtain a pretreated activated carbon carrier; in a nitrogen atmosphere, putting the pretreated activated carbon carrier into a FeSO4 solution, uniformly stirring, and sealing and storing; adding an EDTA solution, and then adding ammonia water; and introducing air, stopping aeration when the pH value is reduced to 4.0-5.0, cleaning, and drying to obtain the heterogeneous catalysis electro-Fenton reaction material. When the voltage of a heterogeneous catalysis electro-Fenton treatment device constructed by the heterogeneous catalysis electro-Fenton reaction material is 1-3V, the removal rate of COD (Chemical Oxygen Demand) on wastewater is greater than or equal to 80%, and after wastewater treatment, the average concentration of COD is less than 25mg / L, and the chromaticity is reduced to 10-30 times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sewage treatment material equipment, and in particular to a preparation method, a treatment device and an application of a heterogeneous catalytic electro-Fenton reaction material. Background Art

[0002] Advanced oxidation technology refers to the technology that produces hydroxyl radicals (·OH) through physicochemical processes such as light, sound, electricity and magnetism. Its redox potential is second only to fluorine, up to +2.80V. By using the strong oxidizing property of ·OH, large molecules and difficult-to-degrade organic matter in wastewater are decomposed into small molecules that are easily biodegradable or completely oxidized and decomposed into CO2 and H2O. At the end of the 19th century, French scientist Fenton invented Fe 2+ Fenton's reagent is a combination of H2O2 and Fe. Eisenhouser first applied Fenton's reagent to wastewater treatment in 1964, and since then Fenton's method has played an important role in environmental chemistry. The standard Fenton's reagent is H2O2 under acidic conditions (pH ≈ 3) and reacts with Fe 2+ The catalytic action of ·OH with high reactivity is generated.

[0003] The traditional Fenton method uses dissolved Fe 2+ The reaction with 2-Hydroxy-2-nitropropene as the catalyst is called homogeneous Fenton technology, which has a good removal effect on persistent organic pollutants, and the reaction is rapid, the reaction conditions are mild, and the operation is simple. It is considered to have broad application prospects in the treatment of toxic, harmful and difficult-to-degrade industrial wastewater. However, the traditional Fenton oxidation process also has some defects: the reaction must be carried out under acidic conditions, so generally acid is added to the wastewater to adjust the pH to 3-5, and then alkali is used to adjust the wastewater to neutral after the reaction is completed, which consumes a lot of acid and alkali and increases the salinity of the wastewater; the reaction will produce a large amount of iron sludge, which is difficult to treat or regenerate; H2O2 and Fe 2+ The utilization rate is low and the processing cost is high.

[0004] In recent years, a series of new Fenton oxidation processes have been developed based on the characteristics of the traditional Fenton method, including Electro-Fenton, Photo-Fenton, Ultrasonic Fenton, Heterogeneous Fenton, etc. The homogeneous Electro-Fenton system is an electrochemical method that continuously produces Fe 2+ , H2O2 is generated in situ or directly added, and the OH produced by the reaction between the two oxidizes the organic matter. 2+The cathode can be regenerated, which reduces the amount of iron sludge produced and the consumption of catalysts, and reduces the operation and treatment costs. However, in the homogeneous Electro-Fenton system, due to the formation mechanism of OH, a large amount of acid and alkali is still required to adjust the pH of the wastewater. In order to further solve the defects of this process, a heterogeneous Electro-Fenton system has been developed. In the heterogeneous Electro-Fenton system, the heterogeneous catalyst often uses precious metals and transition metal oxides as solid phase catalysts, and zeolite molecular sieves, activated carbon, Al2O3, carbon fiber and ceramics as catalyst supports. The heterogeneous Electro-Fenton solves some of the drawbacks of the traditional Fenton reaction, but the reaction catalytic efficiency is lower than that of the traditional Fenton reaction. At the same time, the existing heterogeneous catalysts are expensive, easy to deactivate, short in service life, high in consumption, and difficult to recycle. It is also necessary to modify the heterogeneous Electro-Fenton catalytic electrode materials and rationally design the reaction system to improve the system's performance in removing pollutants.

[0005] The chemical oxygen demand (COD) concentration of the effluent from the biochemical system of coal chemical wastewater is 90-150 mg / L, and the wastewater has a high chromaticity and is brown-yellow. The remaining COD in the wastewater and organic matter containing various chromophores and auxochromes are difficult to degrade compounds, and they cannot be effectively removed simply by extending the hydraulic retention time of the biochemical system. In order for the wastewater to eventually meet the industrial circulating water replenishment standards, the effluent from the biochemical system needs to be deeply treated. Advanced oxidation technologies such as ozone catalytic oxidation and Fenton oxidation are commonly used to treat coal gasification wastewater, but there are still problems such as high reaction energy consumption, large acid and alkali consumption, and high effluent salinity. Summary of the invention

[0006] In view of the deficiencies in the prior art, an object of the present invention is to provide a method for preparing a heterogeneous catalytic electro-Fenton reaction material with high catalytic efficiency, long service life and low cost.

[0007] Another object of the present invention is to provide a heterogeneous catalytic electro-Fenton treatment device constructed using the above-mentioned heterogeneous catalytic electro-Fenton reaction material.

[0008] Another object of the present invention is to provide the application of the above-mentioned heterogeneous catalytic electro-Fenton treatment device in the deep treatment of coal chemical wastewater.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A method for preparing a heterogeneous catalytic electro-Fenton reaction material comprises the following steps:

[0011] S1, measure the columnar activated carbon and remove the ash on its surface;

[0012] In S1, the method for removing surface ash of columnar activated carbon is: washing the columnar activated carbon with deionized water for 2 to 3 times, dispersing the columnar activated carbon in deionized water and heating to boil after washing, wherein the volume ratio of the columnar activated carbon to deionized water is 1:(1 to 2).

[0013] S2, treating the columnar activated carbon treated in S1 to remove grease and inorganic salts in the columnar activated carbon;

[0014] In the S2, the method for removing grease from the columnar activated carbon is: immersing the columnar activated carbon in a 0.5-2.0 mol / L NaOH solution for 0.5-5 h.

[0015] In the S2, the method for removing inorganic salts in the columnar activated carbon is: immersing the columnar activated carbon in a 0.5-2.0 mol / L HCl solution for 12-48 hours.

[0016] S3, washing the columnar activated carbon treated in S2 with deionized water and drying to constant weight to obtain a pretreated activated carbon carrier;

[0017] In S3, the cleaning is performed 2 to 4 times, and the columnar activated carbon is soaked for 0.5 to 2 hours each time.

[0018] S4, placing the pretreated activated carbon carrier in a 0.1-0.3 mol / L FeSO4 solution in a nitrogen-saturated atmosphere, stirring evenly, and sealing to obtain a first activated carbon mixed system;

[0019] In the S4, the volume ratio of the FeSO4 solution and the columnar activated carbon is (1-2):1.

[0020] In S3 and S4, the drying temperature is 50-80°C.

[0021] In S4, the sealed storage time is 12 to 24 hours.

[0022] S5, adding a concentration of 5.0×10 -5 ~10.0×10 -5 mol / L EDTA solution to obtain a second activated carbon mixed system, and adding ammonia water to a pH of 6.0-9.0 under stirring to obtain a third activated carbon mixed system;

[0023] In S5, the volume ratio of the EDTA solution to the columnar activated carbon is (1-2):1.

[0024] S6, introducing air into the third mixed system of activated carbon at 15-30°C, stopping aeration when the pH of the third mixed system of activated carbon drops to 4.0-5.0, taking out the columnar activated carbon and washing it with deionized water, drying it to constant weight, and obtaining a heterogeneous catalytic electro-Fenton reaction material.

[0025] In S6, the flow rate of the air is: 4 to 6 L / min of air is introduced into the third mixed system per liter of activated carbon.

[0026] In S6, the cleaning is performed 2 to 4 times, and the columnar activated carbon is soaked for 0.5 to 2 hours each time.

[0027] In S6, the drying temperature is 50-80°C.

[0028] The heterogeneous catalytic electro-Fenton treatment device constructed by the above-mentioned heterogeneous catalytic electro-Fenton reaction material comprises: a bipotentiostat (1), a constant temperature heating magnetic stirrer (2), and an electrode working chamber (3);

[0029] The electrode working chamber (3) comprises: a stainless steel wire mesh (4), a graphite cathode (5), an inert metal anode (6), the heterogeneous catalytic electro-Fenton reaction material (7) and a perforated partition (8), wherein:

[0030] The perforated partition plate (8) is arranged at the lower part of the electrode working chamber (3) to separate the electrode working chamber (3) into an upper reaction zone and a lower stirring zone;

[0031] The stainless steel wire mesh (4) is vertically arranged in the upper reaction zone to separate the upper reaction zone into an anode chamber and a cathode chamber;

[0032] The heterogeneous catalytic electro-Fenton reaction material (7) is placed at the bottom of the cathode chamber as a catalyst filler;

[0033] The graphite cathode (5) is vertically inserted into the heterogeneous catalytic electro-Fenton reaction material (7);

[0034] The inert metal anode (6) is placed in the anode chamber;

[0035] The electrode working chamber (3) is installed above the constant temperature heating magnetic stirrer (2), and the magnet of the constant temperature heating magnetic stirrer (2) is placed in the lower stirring zone;

[0036] The upper ends of the graphite cathode (5) and the inert metal anode (6) are connected to the bipotentiostat (1).

[0037] In the above technical solution, the effective volume of the electrode working chamber (3) is 500 to 2000 mL.

[0038] In the above technical solution, the effective reaction volume ratio of the anode chamber and the cathode chamber is 1:(2-5).

[0039] In the above technical solution, the filling ratio of the heterogeneous catalytic electro-Fenton reaction material (7) in the cathode chamber is 40-60%.

[0040] In the above technical solution, the inert metal anode (6) is a titanium metal sheet, and the graphite cathode (5) is a graphite rod.

[0041] In the above technical solution, the perforated partition plate (8) is a porous organic glass plate.

[0042] In the above technical solution, the magnetic agitator (2) provided by the constant temperature heating magnetic stirrer has a magnetic rotation speed of 60 to 120 rpm.

[0043] In the above technical solution, the voltage of the DC power supply provided by the bipotentiostat (1) is 1 to 5V.

[0044] The invention discloses an application of a heterogeneous catalytic electro-Fenton treatment device in deep treatment of coal chemical wastewater, comprising the following steps: taking 500-1500 mL of effluent from secondary biochemical treatment of coal gasification wastewater as wastewater and placing it in an electrode working room (3) of the heterogeneous catalytic electro-Fenton treatment device; adding the above-mentioned heterogeneous catalytic electro-Fenton reaction material as catalyst filler into the electrode working room (3); turning on a constant temperature heating magnetic stirrer (2) for magnetic stirring; after the catalyst filler is fully adsorbed and saturated for 10-60 minutes, adding 0.5-3.0 mL of H2O2 per liter of wastewater; and simultaneously turning on a dual constant potentiostat (1) to provide a DC power supply for catalytic electro-Fenton reaction; and conducting the reaction for 60-240 minutes. During the whole reaction process, the magnetic stirrer (2) is kept in an on state.

[0045] In the above technical scheme, after the catalyst filler is fully adsorbed and saturated for 40 minutes, 2.0 mL of H2O2 is added to each liter of wastewater, and at the same time, the bipotentiostat (1) is turned on to provide a DC power supply for catalytic electro-Fenton reaction. The voltage of the DC power supply is 1 V, and the reaction is carried out for 120 minutes.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] 1. The heterogeneous catalytic electro-Fenton reaction material prepared by the preparation method of the present invention has high reaction activity, strong applicability and long service life.

[0048] 2. The heterogeneous catalytic electro-Fenton treatment device (voltage is 1 to 3 V) of the present invention has a COD removal rate of ≥80% for wastewater, and the average COD concentration of the treated wastewater is <25 mg / L, which meets the industrial circulating water replenishment standard; the chromaticity of the wastewater is reduced by 10 to 30 times, and the organic matter containing chromophore groups is efficiently degraded.

[0049] 3. The raw materials for the preparation method of the present invention are easily available, the preparation method is simple, and the material cost is low.

[0050] 4. The present invention adopts a heterogeneous catalytic electro-Fenton treatment device constructed with heterogeneous catalytic electro-Fenton reaction materials, and replaces the traditional soluble metal salt catalyst homogeneous reaction mode with a fixed bed catalytic reaction mode, thereby improving the utilization rate of the heterogeneous catalytic electro-Fenton reaction materials, reducing the reaction cost, and reducing the metal salt concentration in the treated water.

[0051] 5. The heterogeneous catalytic electro-Fenton reaction material of the present invention does not require pH adjustment of wastewater before and after wastewater treatment, thereby reducing the input of acid, alkali and salt consumption, lowering the salinity of the water body, eliminating iron-containing sludge pollution, and generating no secondary pollution, which is green and environmentally friendly.

[0052] 6. The heterogeneous catalytic electro-Fenton reaction material of the present invention uses columnar activated carbon as a carrier, and is loaded with iron oxyhydroxide (FeOOH) through processes such as washing, drying, loading, and aeration in sequence. The loaded FeOOH is composed of mixed crystals of goethite (α-FeOOH) and cellulose ore (γ-FeOOH), with γ-FeOOH being the main component. The single-point pore volume of the heterogeneous catalytic electro-Fenton reaction material after loading is increased, the porosity of the FeOOH particle layer is high, the specific surface area is large, the average pore diameter is 3.82 to 3.10 nm, and the pore size distribution range is increased compared with the original columnar activated carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is a finished product image of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1;

[0054] Figure 2 is a SEM image, wherein a is the activated carbon support prepared in Comparative Example 1, and b is the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1;

[0055] Figure 3 Transmission electron microscope (TEM) images of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 at 200 nm and 100 nm scales, respectively;

[0056] Figure 4 FT-IR spectrum of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1;

[0057] Figure 5The pore size distribution and nitrogen adsorption / desorption curves of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 and the activated carbon carrier prepared in Comparative Example 1;

[0058] Figure 6 The X-ray diffraction spectrum of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1;

[0059] Figure 7 A schematic diagram of a heterogeneous catalytic electro-Fenton treatment system device constructed using the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1;

[0060] Figure 8 This is a diagram showing the removal effect of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 on COD;

[0061] Fig. 9 The figure is a diagram showing the removal effect of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 on COD at different reaction pH values;

[0062] Fig.10 is the COD removal rate of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 at different H2O2 dosages;

[0063] Fig.11 The figure is a diagram showing the removal effect of COD by the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 at different voltages. DETAILED DESCRIPTION

[0064] The preparation method of the present invention is described in detail below with reference to the examples.

[0065] In the following examples, the columnar activated carbon needs to be sealed and stored for future use after drying.

[0066] The NaOH solution, HCl solution, FeSO4 solution and EDTA solution in the following examples are all aqueous solutions.

[0067] Example 1

[0068] A method for preparing a heterogeneous catalytic electro-Fenton reaction material comprises the following steps:

[0069] S1, measure 1L of columnar activated carbon, wash the columnar activated carbon twice with deionized water, disperse it in 1L of deionized water and heat and boil it for 2h to remove the surface ash of the columnar activated carbon;

[0070] S2, placing the columnar activated carbon treated by S1 in a 1 mol / L NaOH solution and soaking it for 2 hours to remove the grease in the columnar activated carbon, and then placing the columnar activated carbon in a 1 mol / L HCl solution and soaking it for 24 hours to remove the inorganic salt in the columnar activated carbon;

[0071] S3, washing the soaked columnar activated carbon with deionized water twice, soaking the columnar activated carbon in deionized water for 30 minutes each time, and then placing it in a blast drying oven, drying it at 80° C. until the columnar activated carbon has a constant weight, to obtain a pretreated activated carbon carrier;

[0072] S4, to prevent oxidation, in a nitrogen-saturated atmosphere, the pretreated activated carbon carrier was placed in 1L of a 0.2mol / L FeSO4 solution, stirred evenly and sealed for 24h to obtain a first activated carbon mixed system;

[0073] S5, add 1L of 7.5×10 -5 mol / L EDTA solution to obtain a second activated carbon mixed system, and under stirring, adding ammonia water to the second activated carbon mixed system to adjust the reaction environment to pH = 9.0 to obtain a third activated carbon mixed system;

[0074] S6, at 20°C, air is introduced at a rate of 5 L / min per liter of the third mixed system of activated carbon. When the pH of the third mixed system of activated carbon drops to 4.5, aeration is stopped. The columnar activated carbon is taken out, washed four times with deionized water, placed in a forced air drying oven, and dried at 50°C until the columnar activated carbon has a constant weight, thereby obtaining a heterogeneous catalytic electro-Fenton reaction material, numbered: FeOOH / AC.

[0075] Figure 1 The heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 is brown-yellow in color due to the generation of iron oxyhydroxide (FeOOH) on the surface of the material. Figure 1 It can be seen that iron oxyhydroxide (FeOOH) is uniformly loaded on the surface of the heterogeneous catalytic electro-Fenton reaction material.

[0076] Comparative Example 1

[0077] A method for constructing an activated carbon carrier, the steps are the same as S1-S3 of Example 1. The prepared activated carbon carrier is numbered: AC.

[0078] Performance Testing

[0079] The heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 and the activated carbon carrier prepared in Comparative Example 1 were tested for relevant electrochemical properties, as follows:

[0080] (1) Scanning electron microscopy (SEM) analysis

[0081] The SEM images of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 and the activated carbon carrier prepared in Comparative Example 1 are as follows: Figure 2As shown, wherein a is the activated carbon carrier prepared in Comparative Example 1, b is the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1, and Figure 2 It can be seen that the surface structure of the activated carbon (AC) carrier prepared in Comparative Example 1 is uneven, and most of them are irregular particles of uneven size. After FeOOH loading, the surface of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 presents a layer of uniform needle-like structures, the covering layer is dense, and the voids in the activated carbon carrier are completely loaded, indicating that the loading experiment effect of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 is good.

[0082] (2) Transmission electron microscopy (TEM) analysis

[0083] The heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 was subjected to transmission electron microscopy analysis and testing. The test results are as follows: Figure 3 As shown, it can be seen that the FeOOH crystals loaded on the heterogeneous catalytic electro-Fenton reaction material present a plate-like or needle-like structure. This is because the FeOOH crystals are composed of a mixture of plate-like α-FeOOH and needle-like γ-FeOOH, and their grain size is uniform, with a thickness of about 5 nm and a length greater than 100 nm.

[0084] (3) Fourier transform infrared spectroscopy (FTIR) analysis

[0085] The heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 was subjected to Fourier transform infrared spectroscopy analysis test. The test results are as follows: Figure 4 As shown, it can be seen that at 3200~3420cm -1 The -OH stretching vibration absorption peak appeared at 1636 cm -1 The absorption peak at 468-894 cm is the -OH bending vibration absorption peak. -1 The absorption peak at 894 cm is the characteristic absorption peak of FeOOH. -1 、795cm -1 and 638cm -1 The absorption peak at 1025cm is the characteristic absorption peak of α-FeOOH. -1 and 746cm -1 The absorption peak at is the characteristic absorption peak of γ-FeOOH. In summary, the FeOOH loaded on the surface of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 is mainly composed of two crystal structures: α-FeOOH and γ-FeOOH.

[0086] (4) Analysis of pore structure, specific surface area and adsorption performance (macroscopic analysis)

[0087] The pore structure, specific surface area and adsorption performance of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 and the activated carbon carrier prepared in Comparative Example 1 were analyzed, and the pore size distribution and nitrogen adsorption / desorption curves obtained were as follows: Figure 5 As shown, it can be seen that after loading FeOOH, the single-point pore volume of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 increases, indicating that the loaded FeOOH particle layer has a large porosity, and also indicating that the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 has a large catalytic surface area. After the activated carbon carrier prepared in Comparative Example 1 is loaded with FeOOH (i.e., the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1), the average pore size decreases from 3.82 nm to 3.10 nm, and the pore size distribution range increases.

[0088] (5) XRD ray diffraction spectrum analysis (quantitative analysis)

[0089] The heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 was subjected to XRD ray diffraction spectrum test for quantitative analysis. Figure 6 As shown. Compared with the standard card of γ-FeOOH (JCPDS 44-1415), the characteristic peaks at 2θ=27°, 36°, 47° and 53° in the XRD spectrum correspond to the characteristic peaks of γ-FeOOH; compared with the standard card of α-FeOOH (JCPDS29-0713), the characteristic peaks at 2θ=21°, 33°, 34°, 58° and 62° in the XRD spectrum correspond to the characteristic peaks of α-FeOOH. It can be seen from the peak intensity of the characteristic peaks that the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 is mainly composed of γ-FeOOH, and also contains a small amount of α-FeOOH.

[0090] In summary, the construction method of the present invention uses FeSO4 and ammonia water as raw materials and columnar activated carbon as a carrier to prepare heterogeneous catalytic electro-Fenton reaction materials. Characterization of the composition, structure and physicochemical properties of the homogeneous catalytic electro-Fenton reaction materials by methods such as SEM, TEM, FT-IR and XRD shows that the FeOOH particles loaded by the heterogeneous catalytic electro-Fenton reaction materials are uniform in size and shape, have excellent catalytic specific surface area, and the FeOOH thereof is mainly in the γ-FeOOH crystal form, and contains a small amount of α-FeOOH.

[0091] Example 2

[0092] A heterogeneous catalytic electro-Fenton treatment device constructed using the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1, the structure of which is as follows Figure 7 As shown, it includes: DJS-292 dual constant potential instrument 1, DF-101S constant temperature heating magnetic stirrer 2, electrode studio 3;

[0093] The electrode working chamber 3 comprises a stainless steel wire mesh 4, a graphite cathode 5, an inert metal anode 6, a heterogeneous catalytic electro-Fenton reaction material 7 and a perforated partition 8, wherein:

[0094] The perforated partition 8 is arranged at the lower part of the electrode working chamber 3, and divides the electrode working chamber 3 into an upper reaction zone and a lower stirring zone. The perforated partition 8 is a porous organic glass plate.

[0095] The stainless steel wire mesh 4 is vertically arranged in the upper reaction zone to separate the upper reaction zone into an anode chamber and a cathode chamber, the effective reaction volume ratio of the anode chamber and the cathode chamber is 1:5, and the filling ratio of the heterogeneous catalytic electro-Fenton reaction material 7 in the cathode chamber is 50%;

[0096] The heterogeneous catalytic electro-Fenton reaction material 7 is placed at the bottom of the cathode chamber as a catalyst filler;

[0097] The graphite cathode 5 is vertically inserted into the heterogeneous catalytic electro-Fenton reaction material 7, and the graphite cathode 5 is a graphite rod;

[0098] The inert metal anode 6 is placed in the anode chamber, and the inert metal anode 6 is a titanium metal sheet;

[0099] The electrode studio 3 is installed above the constant temperature heating magnetic stirrer 2. The magnet of the DF-101S constant temperature heating magnetic stirrer 2 is placed in the lower stirring zone. The rotation speed of the magnet is 100 rpm. The DF-101S constant temperature heating magnetic stirrer 2 is used to drive the wastewater to flow and keep the pollutant concentration of the wastewater uniform.

[0100] The upper ends of the graphite cathode 5 and the inert metal anode 6 are connected to a bipotentiostat 1 to provide a direct current for the reaction, the voltage of which is 2V;

[0101] The electrode working chamber 3 is in the shape of a cylindrical cup with an open top and an effective volume of 1000 mL.

[0102] Example 3

[0103] The wastewater used in this example is the effluent from the secondary biochemical treatment of coal gasification wastewater. In order to reduce the impact of effluent quality fluctuations on the experimental results, the deep treatment experiment uses the effluent from the same batch of biochemical system and stores it at 4°C. The average COD concentration of the biochemical effluent used is 128 mg / L, the chromaticity is 470 times, and the pH is 6.85.

[0104] (1) Adsorption of catalyst

[0105] 1000 mL of wastewater (pH 6.85) was placed in the electrode chamber 3 of the heterogeneous catalytic electro-Fenton treatment device of Example 2, and the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 was placed in the cathode chamber as a catalyst filler, so that the filling ratio of the catalyst filler in the cathode chamber was 50%. The DF-101S constant temperature heating magnetic stirrer 2 was turned on for magnetic stirring, the reaction temperature was controlled at 20°C, and COD was measured every 10 minutes.

[0106] Test results such as Figure 8 As shown, it can be seen that in the first 40 minutes, the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 has a high adsorption rate for COD, and the COD removal rate is linearly related to the adsorption time. The COD removal rate of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 is 22.67%. After 40 minutes, the adsorption rate of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 slows down, and it is determined that the power-on operation of the heterogeneous catalytic electro-Fenton treatment device is carried out after 40 minutes of adsorption.

[0107] (2) Effect of pH on COD removal efficiency

[0108] In order to investigate the effect of pH on COD removal efficiency, the pH of the wastewater was adjusted with 1 mol / L HCl and 1 mol / L NaOH, and the pH of the experimental wastewater was adjusted to 7.0, 6.0, 5.0 and 4.0, respectively.

[0109] COD adsorption experiment: 1000mL of wastewater (pH of 7.0, 6.0, 5.0 and 4.0 respectively) was placed in the electrode working room 3 of the heterogeneous catalytic electro-Fenton treatment device of Example 2, and the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 was placed in the cathode chamber as a catalyst filler, so that the filling ratio of the catalyst filler in the cathode chamber was 50%, and the DF-101S constant temperature heating magnetic stirrer 2 was turned on for magnetic stirring, and the reaction temperature was controlled at 20°C. After the catalyst filler was fully adsorbed and saturated for 40 minutes, H2O2 with an effective concentration of 30% was added to the wastewater, and the H2O2 dosage was 3.0mL / L (relative to the wastewater). At the same time, the DJS-292 dual constant potentiostat 1 was turned on, and the power was turned on. The voltage was set to 2V, and the sampling frequency for the first 50 minutes of power-on operation was once per 10 minutes, and the sampling frequency after 50 minutes of power-on operation was once per 20 minutes. The power-on operation was 130 minutes in total, and the COD was measured as follows: Fig. 9 shown.

[0110] Depend on Fig. 9 It can be seen that when the pH is 4.0, the COD reaction removal rate is the highest, which is 87.27%, and the final concentration of COD is 16.3 mg / L; when the pH is 7.0, the COD reaction removal rate is the lowest, which is 82.89%, and the final concentration of COD is 21.9 mg / L.

[0111] It can be seen from the test results that as the pH decreases, the COD removal rate increases slightly, but the final COD reaction removal rate only differs by 4.38%, which is not obvious, and both meet the industrial circulating water replenishment standard (COD≤60mg / L). Therefore, the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 does not need to adjust the pH, can complete wastewater treatment in one step, and can avoid the problem of increased reagent costs and catalyst filler loss caused by too low pH.

[0112] (3) Effect of H2O2 dosage on COD removal effect

[0113] In order to investigate the effect of H2O2 dosage on COD removal rate, this experiment referred to the “COD adsorption experiment” to test the COD concentration in the wastewater (pH 6.85), and set the H2O2 dosage to 0.5mL / L, 1.0mL / L, 1.5mL / L, 2.0mL / L, 2.5mL / L and 3.0mL / L, respectively. The experiment was repeated three times for each concentration batch. After 40 minutes of adsorption, the DJS-292 dual constant potentiostat was turned on, the voltage was set to 2V, and the power was turned on for 120 minutes. After the power was turned on, the average COD removal rate of the repeated experiments was taken.

[0114] The experimental results are as follows Fig.10 As shown by Fig.10 It can be seen that when the H2O2 dosage is less than 2.0mL / L, the COD removal rate increases with the increase in the H2O2 dosage. At a H2O2 dosage of 2.0mL / L, the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 has the maximum removal of COD in wastewater, with a COD removal rate of 85.1%. When the H2O2 dosage is further increased, the COD removal rate decreases slightly, but still remains at about 84%.

[0115] (4) Effect of reaction tank pressure (voltage) on COD removal effect

[0116] In order to investigate the effect of the voltage of the external DC power supply on the COD removal effect, this experiment refers to the "COD adsorption experiment" to test the COD concentration in the wastewater (pH 6.85, H2O2 dosage 2.0mL / L), and the voltage of the DC power supply is set to 1V, 2V, 3V and 4V respectively. After 40 minutes of adsorption, the DJS-292 dual constant potentiostat is turned on and powered on. Sampling and testing are performed every 20 minutes, and the total power supply is 120 minutes. The experimental results are shown in the figure. Fig.11 shown.

[0117] Fig.11The figure is a diagram of the COD removal effect of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 under different voltages. When the voltage is 1V to 3V, the COD removal rate of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 is about 83%, and the final COD concentration is 20mg / L. When the voltage is increased to 4V, the COD removal rate of the heterogeneous catalytic electro-Fenton reaction material prepared in Example 1 decreases, the final COD concentration increases to 37mg / L, and the COD removal rate decreases to 71.09%. Considering the treatment effects and energy consumption costs under different reaction voltages, the reaction tank voltage is selected to be 1V.

Claims

1. A method for preparing a heterogeneous catalytic electro-Fenton reaction material, characterized in that: The following steps are involved: S1, measure the columnar activated carbon and remove the ash on its surface; S2, treating the columnar activated carbon treated in S1 to remove grease and inorganic salts in the columnar activated carbon; S3, washing the columnar activated carbon treated in S2 with deionized water and drying to constant weight to obtain a pretreated activated carbon carrier; S4, placing the pretreated activated carbon carrier in a 0.1-0.3 mol / L FeSO4 solution in a nitrogen-saturated atmosphere, stirring evenly, and sealing to obtain a first activated carbon mixed system; S5, adding a concentration of 5.0×10 -5 ~10.0×10 -5 mol / L EDTA solution to obtain a second activated carbon mixed system, and adding ammonia water to a pH of 6.0-9.0 under stirring to obtain a third activated carbon mixed system; S6, introducing air into the third mixed system of activated carbon at 15-30°C, stopping aeration when the pH of the third mixed system of activated carbon drops to 4.0-5.0, taking out the columnar activated carbon and washing it with deionized water, drying it to constant weight, and obtaining a heterogeneous catalytic electro-Fenton reaction material.

2. The preparation method according to claim 1, characterized in that: In S4, the volume ratio of the FeSO4 solution and the columnar activated carbon is (1-2):1; In S5, the volume ratio of the EDTA solution to the columnar activated carbon is (1-2):

1.

3. The preparation method according to claim 1, characterized in that: The method for removing surface ash of columnar activated carbon in S1 is: washing the columnar activated carbon with deionized water for 2 to 3 times, dispersing the columnar activated carbon in deionized water and heating to boil after washing, wherein the volume ratio of the columnar activated carbon to deionized water is 1:(1 to 2).

4. The preparation method according to claim 1, characterized in that: The method for removing grease from columnar activated carbon in S2 is: soaking the columnar activated carbon in a 0.5-2.0 mol / L NaOH solution for 0.5-5 h; The method for removing inorganic salts from columnar activated carbon in S2 is: immersing the columnar activated carbon in a 0.5-2.0 mol / L HCl solution for 12-48 hours.

5. The preparation method according to claim 1, characterized in that: The number of cleanings in S3 is 2 to 4 times, and the columnar activated carbon is soaked for 0.5 to 2 hours each time; The drying temperature in S3 and S4 is 50-80°C; The sealed storage time in S4 is 12 to 24 hours; In S6, the air flow rate is: 4 to 6 L / min of air is introduced into the third mixed system per liter of activated carbon; the number of cleanings is 2 to 4 times, and the columnar activated carbon is soaked for 0.5 to 2 hours each time; and the drying temperature is 50 to 80°C.

6. A heterogeneous catalytic electro-Fenton treatment device constructed by the heterogeneous catalytic electro-Fenton reaction material obtained by the preparation method according to any one of claims 1 to 5, characterized in that: include: A dual potentiostat (1), a constant temperature heating magnetic stirrer (2), and an electrode studio (3); The electrode working chamber (3) comprises a stainless steel wire mesh (4), a graphite cathode (5), an inert metal anode (6), the heterogeneous catalytic electro-Fenton reaction material (7) and a perforated partition (8), wherein: The perforated partition plate (8) is arranged at the lower part of the electrode working chamber (3) to separate the electrode working chamber (3) into an upper reaction zone and a lower stirring zone; The stainless steel wire mesh (4) is vertically arranged in the upper reaction zone to separate the upper reaction zone into an anode chamber and a cathode chamber; The heterogeneous catalytic electro-Fenton reaction material (7) is placed at the bottom of the cathode chamber as a catalyst filler; The graphite cathode (5) is vertically inserted into the heterogeneous catalytic electro-Fenton reaction material (7); The inert metal anode (6) is placed in the anode chamber; The electrode working chamber (3) is installed above the constant temperature heating magnetic stirrer (2), and the magnet of the constant temperature heating magnetic stirrer (2) is placed in the lower stirring zone; The upper ends of the graphite cathode (5) and the inert metal anode (6) are connected to the bipotentiostat (1).

7. The heterogeneous catalytic electro-Fenton treatment device according to claim 6, characterized in that: The effective volume of the electrode working chamber (3) is 500 to 2000 mL; The effective reaction volume ratio of the anode chamber to the cathode chamber is 1:(2-5); The filling ratio of the heterogeneous catalytic electro-Fenton reaction material (7) in the cathode chamber is 40-60%.

8. The heterogeneous catalytic electro-Fenton treatment device according to claim 7, characterized in that: The inert metal anode (6) is a titanium metal sheet, and the graphite cathode (5) is a graphite rod; The perforated partition (8) is a porous organic glass plate; The constant temperature heating magnetic stirrer (2) provides a magnetic sub-rotation speed of 60 to 120 rpm; The voltage of the DC power supply provided by the bipotentiostat (1) is 1 to 5V.

9. Application of the heterogeneous catalytic electro-Fenton treatment device according to claim 8 in deep treatment of coal chemical wastewater, characterized in that: 500-1500 mL of the effluent from the secondary biochemical treatment of coal gasification wastewater is taken as wastewater and placed in the electrode working room (3) described in claim 6, and the heterogeneous catalytic electro-Fenton reaction material obtained by the preparation method described in any one of claims 1 to 5 is added into the electrode working room (3) as a catalyst filler, and the constant temperature heating magnetic stirrer (2) described in claim 6 is turned on for magnetic stirring. After the catalyst filler is fully adsorbed and saturated for 10 to 60 minutes, 0.5 to 3.0 mL of H2O2 is added to each liter of wastewater, and the bipotentiostat (1) is turned on to provide a DC power supply for catalytic electro-Fenton reaction. The reaction is powered on for 60 to 240 minutes, and the magnetic stirrer (2) is kept on during the entire reaction process.

10. The use according to claim 9, characterized in that: After the catalyst filler was fully adsorbed and saturated for 40 minutes, 2.0 mL of H2O2 was added to each liter of wastewater, and the bipotentiostat (1) was turned on to provide a DC power supply for catalytic electro-Fenton reaction. The voltage of the DC power supply was 1 V, and the reaction was carried out for 120 minutes.

Citation Information

Patent Citations

  • Preparation method of supported FeOOH catalyst, and electro-Fenton waste water treatment system

    CN102218319A

  • Heterogeneous electro-Fenton catalyst as well as preparation method and application thereof

    CN114832822A

  • Supported heterogeneous Fenton catalyst as well as preparation method and application thereof

    CN116393176A

  • Method for treating hardly biodegradable organic matter-containing water

    JP2013208562A

  • Device and method for selective oxidation of macromolecular organic pollutants using free radicals produced in heterogeneous fenton reaction

    US20220315455A1